"A Horrible Looking Woman": Female Violence in Late-Victorian East London. (2nd September 2015) - August, Andrew
Abstract: Scholars have attributed a steep decline in violent crime in nineteenth-century England to a "civilizing offensive" launched to discipline violent masculinities. In East London, however, a significant minority of those brought before summary courts on charges of violent offenses were women. Newspaper accounts of these cases show that some women committed assaults that resembled the violent actions of men. The courts and newspapers evaluated defendants against standards of femininity. Those women who successfully performed dominant versions of femininity received lenient treatment in the courts and approval in the newspapers. The courts harshly punished those who did not conform. These accounts reveal a campaign against disorderly femininities that paralleled the civilizing offensive directed against unruly masculinities.